2018
DOI: 10.1101/334979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TMEM135 is an LXR-inducible regulator of peroxisomal metabolism

Abstract: Summary 24The liver x receptors (LXRs) are key regulators of systemic lipid metabolism. We identified 25 transmembrane protein 135 (TMEM135), a peroxisomal protein with an unknown function, as a 26 novel LXR target gene. The LXRs directly induce TMEM135 transcription in humans via an LXR 27 response element in the 5' untranslated region, but do not increase Tmem135 in murine cells. 28Functionally, knockdown of TMEM135 in vitro and in vivo results in many features typical of 29 peroxisomal disorders such as ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The associated gene identified at the other novel locus, TMEM135 (p = 1.80e-8) is located 1MB ( Fig 6 ) downstream of the identified GWAS locus (the PICALM locus), and two of the identified eQTLs of TMEM135 by our method were located at the GWAS loci (rs536841: p = 5.27e-14 and rs541458: p = 5.67e-12). On the other hand, TMEM135 is a target gene for liver X receptors (LXR), which is involved in removing excessive cholesterol from peripheral tissues [ 53 ]. Increased cholesterol levels in brain tissue are associated with accumulated AβPP [ 51 ] suggesting the potential role of LXR and TMEM135 in the etiology of AD.…”
Section: Resultsmentioning
confidence: 99%
“…The associated gene identified at the other novel locus, TMEM135 (p = 1.80e-8) is located 1MB ( Fig 6 ) downstream of the identified GWAS locus (the PICALM locus), and two of the identified eQTLs of TMEM135 by our method were located at the GWAS loci (rs536841: p = 5.27e-14 and rs541458: p = 5.67e-12). On the other hand, TMEM135 is a target gene for liver X receptors (LXR), which is involved in removing excessive cholesterol from peripheral tissues [ 53 ]. Increased cholesterol levels in brain tissue are associated with accumulated AβPP [ 51 ] suggesting the potential role of LXR and TMEM135 in the etiology of AD.…”
Section: Resultsmentioning
confidence: 99%
“…In PMP52 knockdown mice a few peroxisomal matrix proteins – ACAA1 and SCP2 – were mislocalized to the cytosol which suggests a role of PMP52 in peroxisomal matrix protein import ( Renquist et al, 2018 ). In the same study, an increased level of triglycerides was found in HepG2 cells with a knockdown of PMP52 ( Renquist et al, 2018 ).…”
Section: Peroxisomal Solute Importmentioning
confidence: 99%
“…In PMP52 knockdown mice a few peroxisomal matrix proteins – ACAA1 and SCP2 – were mislocalized to the cytosol which suggests a role of PMP52 in peroxisomal matrix protein import ( Renquist et al, 2018 ). In the same study, an increased level of triglycerides was found in HepG2 cells with a knockdown of PMP52 ( Renquist et al, 2018 ). Finally, in two different mouse models in which either very long-chain acyl-CoA dehydrogenase (VLCAD) or long-chain acyl-CoA dehydrogenase (LCAD) were disrupted, PMP52 levels were significantly elevated.…”
Section: Peroxisomal Solute Importmentioning
confidence: 99%
“…Mitochondria and peroxisomes both oxidize LCFAs (C14–C18), whereas only peroxisomes oxidize very-long-chain fatty acids (VLCFAs, >C20) [ 54 ]. Renquist et al used electrophoretic mobility shift assay (EMSA) and chromatic immunoprecipitation (ChIP) analysis to demonstrate that the human TMEM135 promoter contains a liver X receptor (LXR) response element that binds LXRs and mediates LXR-induced transcription [ 12 , 55 ]. This response element was notably not found in murine cells [ 56 ].…”
Section: Tmem135 and Peroxisomal Transportmentioning
confidence: 99%
“…Consistent with increased fatty acid uptake and beta-oxidation, fasting augmented hepatic fatty acid and NADH concentrations in control mice. Compared with the control mice, fasted TMEM135-knockdown mice displayed a further increase in hepatic fatty acid concentrations and a significant decrease in NADH concentration, suggesting impairment of peroxisomal beta-oxidation [ 55 ]. The peroxisomal contribution to overall LCFA beta-oxidation becomes greater during physiological states of increased fatty acid load, such as fasting, which might partly explain why TMEM135 protein levels were increased in heart and skeletal muscle during fasting and cold stress in mice [ 1 ].…”
Section: Tmem135 and Peroxisomal Transportmentioning
confidence: 99%